WUJUD KEBUDAYAAN DALAM PROSESI BARODAK RITUAL ADAT PERNIKAHAN SUMBAWA - Novi Widya Utami (Universitas Negeri Makassar, 2016)
Abstract: Being Culture in Traditional Marriage Ritual Procession Barodak Sumbawa. This study aimed to describe the cultural community through the procession barodak Sumbawa Sumbawa marriage customs. The method used in this research is descriptive method with qualitative research. The data analysis stage to the stage of transcription, classification, data analysis, and conclusions. To find a form of culture as a complex of ideas, ideas, values, norms, rules and so on; culture form as a complex pattern of activity and action of man in society; and culture form as objects of human work. Based on data analysis, it can be concluded that, found the culture as a complex of ideas, ideas, values, norms, rules and so on; culture form as a complex pattern of activity and action of man in society; and culture form as objects of human work. The third manifestation of this, states of matter and form of activity is the most concrete form to be observed so that the system Sumbawa culture in society can be understood because the reflected predominantly in the form of a second.